KONSEP KEADILAN DAN KEDAULATAN DALAM PERSPEKTIF ISLAM DAN BARAT - Nurdin Nurdin (Media Syari'ah, 2017)
This article to explain about concept justice and sovereignty in Islamic and West perspectives. The justice and sovereignty concept in Islamic perspective are based from Allah (The God) to the people and universally. While the justice and sovereignty concept in West perspective are based from the human views and adjectively special for a community in the people. That different between Islamic views and West just on the basic and theory but it substances are to save convenience and life peace for the people